REGULATION OF THE SYSTEMIC INFLAMMATORY RESPONSE IN PATIENTS WITH MULTIFOCAL ATHEROSCLEROSIS - Anastasia Valerievna Ponasenko; Maria Vladimirovna Khutornaya; Anna Victorovna Sinitskaya; Olga Leonidovna Barbarash (Байкальский медицинский журнал)
Introduction. Data on the role of inflammation in the progression and manifestation of multifocal atherosclerosis (MFA) are contradictory. The systemic process of multiple lesions of different vascular beds in patients with an established diagnosis of coronary heart disease (CHD) is due to several parallel pathological mechanisms. In general, in the pathogenesis of both coronary atherosclerosis and atherosclerosis of peripheral arteries, one of the factors is the variability of immune response genes and cytokines, regulators of the inflammatory response.The aim of this work was to determine the role of variability in the genes of cytokines and innate immune response receptors in the structure of mechanisms associated with the development of MFA in patients with coronary artery atherosclerosis.Materials and methods. 260 patients with CAD (mean age 58 years) were examined. Of all those included in the study, at the time of the survey, MFA was found in 180 people (69.23%), while the incidence of MFA in men and women is comparable (70.33 vs. 64.71%, respectively). There is also no significant difference in the incidence of MFA in the two age groups (up to 60 years, 45% have lesions of two or more vascular beds, and in people older than 60 years, MFA was found in 55% of cases). All patients were informed about the course of the study and voluntarily signed an informed consent. Blood was collected from the cubital vein into Vacutainer tubes with K3EDTA. DNA isolation was carried out using the phenol-chloroform extraction method. Genotyping of 47 polymorphic sites with a single nucleotide change (SNV) of 19 genes proven to be associated with the regulation of the systemic inflammatory response (cytokines, innate immunity receptors) was performed in a 96-well format using TaqMan technology (LifeTechnologies, USA) and real-time result detection with using the ViiATM 7 RealTime PCR System (LifeTechnologies, USA) for polymerase chain reaction in accordance with the instructions. Associations were analyzed using Snpstats (https://www.snpstats.net/start.htm). Odds ratio (OR) and 95% CI for OR were calculated for risk assessment.Results. One association has been established that demonstrates a negative impact and increases the risk of developing MFA in young and middle age. Carriage of the G rs11685424 IL1RL1 allele increases the risks of earlier development of peripheral arterial lesions by 2 times (OR 2.11 (95% CI 1.09-4.06), p = 0.024) according to the recessive inheritance model. At the same time, variability in three sites (rs1974675; rs6758936; rs3755276) of the IL18 receptor gene (IL18R1) reduces the risk of MFA detection by three times (p=0.12; p=0.034: p=0.026, respectively) and this pattern is also observed in patients older age group. In the carriers of the A/A rs1974675, T/T rs3755276 and A/A rs6758936 genotypes in persons over 60 years of age, MFA was diagnosed less frequently (p=0.024; p=0.037; p=0.011, respectively).Conclusion. It has been shown that in patients with significant coronary atherosclerosis, the progression of peripheral vascular atherosclerosis is more associated with the variability of the genes responsible for the regulation of the systemic inflammatory response, rather than genes and their variants that determine the severity and strength of the immune response.